How Rhodium(I)-Catalyzed Phosphorus(III)-Directed C–H Bond Functionalizations Can Improve the Catalytic Activities of Phosphines - Zhang, Zhuan; Durand, Natacha; Soulé, Jean-François (Synlett, 2022)
Trivalent-phosphorus-containing molecules are widely used in fields ranging from catalysis to materials science. Efficient catalytic methods for their modifications, providing straightforward access to novel hybrid structures with superior catalytic activities, are highly desired to facilitate reaction improvement or discovery. We have recently developed new methods for synthesizing polyfunctional phosphines by C–C cross-couplings through rhodium-catalyzed C–H bond activation. These methods use a native P(III) atom as a directing group, and can be used in regioselective late-stage functionalization of phosphine ligands. Interestingly, some of the modified phosphines outperform their parents in Pd-catalyzed cross-coupling reactions.1 Introduction2 Early Examples of Transition-Metal-Catalyzed P(III)-Directed C–H Bond Activation/Functionalizations3 Synthesis of Polyfunctional Biarylphosphines by Late-Stage Alkylation: Application in Carboxylation Reactions4 Synthesis of Polyfunctional Biarylphosphines by Late-Stage Alkenylation: Application in Amidation Reactions5 Conclusion
Keywords: phosphines; C–H bond activation; late-stage functionalization; rhodium catalysis; CO2 fixation; ligands